“WE ARE IN A POSITION OF POWER”: FRONT-LINE WORKERS’ EXPERIENCES AT THE INTERSECTION OF CHILD WELFARE AND IMMIGRATION - Parada, Henry; Ungara, Danielle; Swardh, Kristin; Escobar Olivo, Veronica (Canadian Social Work Review / Revue canadienne de service social, 2024)
This article focuses on the compounding systemic issues that children and families face when involved with immigration and child welfare. Fourteen semi-structured interviews and one focus group (six participants) were conducted with service providers working in social service sectors related to immigration and child welfare who deliver services in Ontario, Canada. Front-line workers’ perspectives were analyzed through a descriptive phenomenological study, revealing how their perceptions of complex trauma histories, systemic oppression, and power dynamics influenced refugees’ experiences and fears regarding the child welfare system. The study emphasizes the need for an anti-oppressive, trauma-informed approach and specialized services for refugee children and families. Conceptualizations of structural social work and trauma-informed practice are drawn on to guide the analysis.